Gastrointestinal bleeding following traumatic brain injury: A clinical study on predisposing factors and outcomes - Mehdi Mahmoodkhani; Arvin Naeimi; Amirhosein Zohrehvand; Masih Sabouri; Mohammad Heidari (Babol University of Medical Sciences, 2024)
Background: Traumatic brain injury (TBI) is one of the most common causes of death and disability worldwide. Stress ulcers are common in critically ill patients and can lead to life-threatening gastrointestinal bleeding (GIB). This study investigates the impact of predisposing factors on GIB and outcomes of TBI patients. Methods: This retrospective cohort study included TBI patients admitted between February 2019 and November 2021. Patients' demographic information and clinical characteristics were collected and divided into Post-TBI GIB and No-GIB groups. During clinical follow-up, the Glasgow Outcome Score (GOS) and mortality were assessed. The correlation between predisposing factors and GIB was investigated. Results: Out of 164 eligible patients, 66.5% were males, and the mean age was 31.38 ± 13.44 years. There was a higher rate of severe TBIs (p<0.001), intra-axial lesions (P=0.014), hypotension at admission (p<0.001), and concurrent coagulopathies (p<0.001) in the Post-TBI GIB group compared to the No-GIB group. In contrast, the Glasgow Coma Scale level upon admission and discharge (p<0.001) and serum hemoglobin level at admission (p<0.001) were lower in the Post-TBI GIB group than in the other group. Moreover, primary GCS (P=0.017) and hypotension at admission (P=0.009), spinal injury (P=0.028), and intra-axial brain injury (P=0.018) were independently associated with GIB in TBI patients. Conclusion: Primary GCS and hypotension at admission, spinal injury, and intra-axial brain injury are independent predictors for GIB in TBI patients. The presence of GIB in TBI patients is associated with worse neurological outcomes as assessed by GOS at approximately 18 months.